The impact of securitization on the expansion of subprime credit - Nadauld, Taylor D.; Sherlund, Shane M. (Journal of Financial Economics, 2013)
This paper investigates the relationship between securitization activity and the extension of subprime credit. The analysis is motivated by two sets of compelling empirical facts. First, the origination of subprime mortgages exploded between the years 2003 and 2005. Second, the securitization of subprime loans increased substantially over the same time period, driven primarily by the five largest independent broker/dealer investment banks. We argue that the relative shift in the securitization activity of investment banks was driven by forces exogenous to factors impacting lending decisions in the primary mortgage market and resulted in lower ZIP code denial rates, higher subprime origination rates, and higher subsequent default rates. Consistent with recent findings in the literature, we provide evidence that the increased securitization activity of investment banks reduced lenders' incentives to carefully screen borrowers.